Factors Related To Female University Students’ Genital Hygiene Status In Universities In Depok Area: Ratna Sari Dewi - Dewi, Ratna Sari (Jurnal Persada Husada Indonesia, 2019)
Transmission of bacteria from the anus to the urethra and vaginal orifice in women caused by genital hygiene status is not well preserved can cause an infection in the urogenital system. The purpose of this research is to get the picture of genital hygiene status in female university students at several universities in Depok. This study uses a Cross sectional method. A questioner was completed by 365 female university students which were taken by Cluster sampling. Univariate analysis reveals the picture of genital hygiene status is poor (78,6%). The result from this study recommends the students to pay more attention to genital hygiene in college and for health education workers to give education about the importance of genital hygiene